The clinical applicability of a daily summary of patients’ self‐reported postoperative pain—A repeated measure analysis - Wikström, Lotta; Eriksson, Kerstin; Fridlund, Bengt; Nilsson, Mats; Årestedt, Kristofer; Broström, Anders (Journal of clinical nursing, 2017)
Aim and objectives (i) To determine whether a central tendency, median, based on patients’ self‐rated pain is a clinically applicable daily measure to show patients’ postoperative pain on the first day after major surgery (ii) and to determine the number of self‐ratings required for the calculation of this measure. Background Perioperative pain traits in medical records are difficult to overview. The clinical applicability of a daily documented summarising measure of patients’ self‐rated pain scores is little explored. Design A repeated measure design was carried out at three Swedish country hospitals. Methods Associations between the measures were analysed with nonparametric statistical methods; systematic and individual group changes were analysed separately. Measure I: pain scores at rest and activity postoperative day 1; measure II: retrospective average pain from postoperative day 1. Results The sample consisted of 190 general surgery patients and 289 orthopaedic surgery patients with a mean age of 65; 56% were men. Forty‐four percent had a pre‐operative daily intake of analgesia, and 77% used postoperative opioids. A range of 4‒9 pain scores seem to be eligible for the calculation of the daily measures of pain. Rank correlations for individual median scores, based on four ratings, vs. retrospective self‐rated average pain, were moderate and strengthened with increased numbers of ratings. A systematic group change towards a higher level of reported retrospective pain was significant. Conclusions The median values were clinically applicable daily measures. The risk of obtaining a higher value than was recalled by patients seemed to be low. Applicability increased with increased frequency of self‐rated pain scores and with high‐quality pain assessments. Relevance to clinical practice The documenting of daily median pain scores at rest and during activity could constitute the basis for obtaining patients’ experiences by showing their pain severity trajectories. The measures could also be an important key to predicting postoperative health‐related consequences.